Juridical Analysis of Court Decision Number 275/Pid.Sus/2019/Pn.Sby About the Word Idiot - Herni Eva Wulandari; Emy Rosnawati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the legal considerations made by the judge to sentence the defendant in a criminal case of insulting idiots in Ahmaddhaniprast's Instagram vlog. This research is based on the judge's decision which does not pay attention to the juridical facts and only pays attention to the indictment and the demands of the Public Prosecutor. Methods This research uses a normative legal research type that examines primary legal materials and secondary legal materials using the following approaches: legislation approach; and case approach, as well as descriptive qualitative analysis of legal materials. The results of this study indicate that the legal considerations made by the Judge in Decision No. 275/Pid.Sus/2019/Pn.Sby., only paid attention to the Indictment and the demands of the Public Prosecutor and ignored the Defendant's Statements, Witness Statements, Expert Witness Statements and Evidence. in the trial, so that the judge's decision is not in accordance with the legal facts that occurred. The judge was not right in applying the rules in making a decision based on Article 27 paragraph (3) ITE by referring to Articles 310 and 311 of the Criminal Code regarding blasphemy and slandering someone who has committed a certain act, due to the fact that idiotic remarks were not directed or accused at someone. The judge should have enforced the provisions of Article 27 paragraph (3) of the ITE Law by referring to Article 315 of the Criminal Code, because the element of light humiliation (eenvoudige belediging) was fulfilled as stated by witnesses, expert witnesses and the statements of the Defendant.